Streptococcal infection and its antimicrobial resistance profile associated with bovine mastitis in Ethiopia: a systematic review and meta-analysis - Fenta, Melkie Dagnaw; Getahun Feleke, Melaku; Mebratu, Atsede Solomon; Mengistu, Bemrew Admassu; Demessie, Yitayew (Frontiers in Veterinary Science, 2025)
BackgroundIn Ethiopia, bovine mastitis is a major problem affecting production, welfare, and public health. Streptococcus is a key pathogen that causes mastitis and is often treated with antimicrobials, which can lead to antimicrobial resistance. Nevertheless, the administration of antimicrobials can unintentionally facilitate the emergence of antimicrobial resistance. Thus, this study aimed to systematically review and estimate the pooled prevalence of streptococcal infection in bovine mastitis in Ethiopia, along with associated antimicrobial resistance profiles, to provide a comprehensive understanding of the current situation and guide effective treatment this bacteria.MethodsThis systematic review was carried out according to the PRISMA guidelines. To estimate the pooled proportion and resistance, a random effects model was utilized with R software. The databases used included SCOPUS, PubMed, HINARI, Web of Science, Google, and Google Scholar.ResultsTwenty-five articles were included in this meta-analysis. The overall pooled proportion of mastitis associated with Streptococcus spp. was 20% (95% CI: 17–23%). Significant heterogeneity was observed in the studies included (I2 = 87%; p < 0.01). Among the regions, the highest proportion was reported for South Nation, Nationality of Peoples Region (SNNPR) at 26%, followed by Amhara (24%), Oromia and Addis Abeba (19%), and Tigray (15%). The highest proportion of Streptococcus isolates was found in patients with clinical mastitis (24%). Among the major Streptococcus spp., Str. agalactiae had the highest pooled prevalence at 13%. The greatest prevalence of resistant Streptococcus was observed against penicillin (52%), followed by streptomycin, tetracycline, and ampicillin (42, 38, and 35%, respectively). According to the information provided by this meta-analysis, evidence-based risk management measures should be established to prevent and control streptococcal infection in dairy cattle. Monitoring and reporting of streptococcal mastitis and antimicrobial resistance are needed in Ethiopia’s different regions. To minimize resistance, stricter guidelines should be implemented for antimicrobial use in dairy cattle, with a particular focus on reducing penicillin use.